2014
DOI: 10.2298/tsci1403731p
|View full text |Cite
|
Sign up to set email alerts
|

Croatia's rural areas - renewable energy based electricity generation for isolated grids

Abstract: Several Western Balkan states face the consequences of the Yugoslavian war, which left hometowns with dilapidated electricity grid connections, a high average age of power plant capacities and low integration of renewable energy sources, grid bottlenecks and a lack of competition. In order to supply all households with electricity, UNDP Croatia did a research on decentralized supply systems based on renewable energy sources. Decentralized supply systems offer cheaper electricity connections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It can be seen that the share of WPS and PHES system varies between 24.9-61.4% and 7. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].5%, respectively. Although an energy storage facility is used, grid connection was necessary to ensure continuous energy flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the share of WPS and PHES system varies between 24.9-61.4% and 7. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].5%, respectively. Although an energy storage facility is used, grid connection was necessary to ensure continuous energy flow.…”
Section: Resultsmentioning
confidence: 99%
“…Renewables are used in a variety of applications including water pumping and also numerous studies about it can be found in the literature [4][5][6][7][8][9][10]. Application of solar energy to cover the energy demand of deep well water pumps for water supply in rural or isolated zones was discussed by Ramos and Ramos [4].…”
Section: Introductionmentioning
confidence: 99%
“…At present, Croatia's electrification rate is 99% [30], or 96.5% when considering a value estimated by a satellite detecting night time lighting [30]. Decentralized supply systems might provide cheaper electricity and enhance the development of these rural areas [32].…”
Section: Electricity Marketmentioning
confidence: 99%
“…Some of the land used for agriculture in the world and also in Turkey has no access to an electricity grid. Therefore, mechanical power from tractors or Diesel generators facilitate the irrigation from wells, streams or canals [3]. For instance, seventy million farms in India use THERMAL SCIENCE: Year 2019, Vol.…”
Section: Introductionmentioning
confidence: 99%